Recent trend of bacterial aetiology of lower respiratory tract infection in a tertiary care centre of Nepal - Mishra, SK; Kattel, HP; Acharya, J; Shah, NP; Shah, AS; Sherchand, JB; Rijal, BP; Pokhrel, BM (International Journal of Infection and Microbiology, 2012)
INTRODUCTION: Lower respiratory tract infections (LRTIs) are among the most common infectious diseases of humans. This study focused on determining the recent trend of bacterial aetiology of LRTIs among the patients attending Tribhuvan University Teaching Hospital (TUTH) in Kathmandu. MATERIALS AND METHODS: This was a prospective study conducted over a period of six months in the bacteriology laboratory of TUTH. A total of 1120 specimens representing lower respiratory tract were received from patients with suspected LRTIs. The specimens were collected and processed according to standard methodology. RESULTS: Respiratory pathogens were recovered from 44.4% cases (n=497). Gram-negative bacteria were recovered in 84.1% (n=488). Bacteria were more commonly recovered from endotracheal secretion (41/61, 67.2%) than in sputum (454/1039, 43.7%) and bronchial washing (2/20, 10%). Ninety-one percent (n=454) growth was monomicrobial while the rest accounted for mixed growth. Among the organisms isolated, Haemophilus influenzae (112, 21%) was the most predominant pathogen followed by Klebsiella pneumoniae (102, 19.1%), Pseudomonads (91, 17.1%), Acinetobacter baumannii calcoaceticus complex (60, 10.9%), Streptococcus pneumoniae (46, 8.6%), Escherichia coli (37, 6.9%). CONCLUSIONS: H. influenzae and S. pneumoniae were the most common Gram-negative and Grampositive bacterial isolates recovered, respectively from LRTIs urging for monitoring and surveillance of these pathogens. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6639 Int J Infect Microbiol 2012;1(1):3-8